Contributions to the morphology and histology of the genital system of the pulmonate Cochlicella ventricosa (Draparnaud) - Els, W. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1966.